Reliability of systems for skier biomechanics analysis: From lab testing to on-slope performance - Cuniberti, G. C.; Costa, I.; Bortolan, L. (10th International Congress on Science and Skiing, January 28 - February 1, 2025, Val di Fiemme, Italy, 2025)
INTRODUCTION: Alpine skiing is a popular sport at both amateur and competitive levels, characterized by complex biomechanics. However, research on skiing biomechanics is limited due to the challenges of replicating real-world conditions in controlled environments and conducting on-field studies where conditions are variable. Technological advancements have made it easier to use equipment even in difficult environments. In movement analysis, motion capture (MoCap) systems provide valuable data for training and injury prevention, with passive marker-based systems being the gold standard in laboratories. However, these systems are less effective outdoors due to sunlight and snow reflections1, while inertial MoCap systems are more practical for outdoor conditions2. This study compares various measurement systems for assessing skier biomechanics, focusing on their effectiveness in capturing key movement parameters and forces in both simulated and real on-slope conditions.